First microscopic and molecular parasitological survey of Strongylus vulgaris in Brazilian ponies - André Vianna Martins; Aline de Lima Coelho; Laís Lisboa Corrêa; Mariana Santos Ribeiro; Lucas Fernandes Lobão; João Pedro Siqueira Palmer; Lucas Cavalcante de Moura; Marcelo Beltrão Molento; Alynne da Silva Barbosa (Revista Brasileira de Parasitologia Veterinária, 2023)
Abstract The frequency of gastrointestinal parasites with an emphasis on Strongylus vulgaris was investigated among the Brazilian Pony breed kept on farms in the municipality of Teresópolis, state of Rio de Janeiro. Fecal samples were collected in three stud farms: A (n= 22 animals), B (n= 3), and C (n= 2). Fecal samples were subjected to the quantitative Mini-FLOTAC technique, using three different solutions, and to qualitative techniques. The parasite prevalence was found to be 81.4%. Eggs from strongylids were identified in 74% of the ponies. Eggs of Parascaris spp. were detected in 22.7% of the animals, which were all females of farm A. At this locality, mares were kept with their foals in fenced paddocks all the time. The NaCl solution of d = 1.200 g/ml was generally the one that presented the highest frequency of diagnosis of nematode eggs and the highest mean of fecal eggs per gram. The fecal samples were also subjected to the polymerase chain reaction for amplification of DNA from the ITS2 region for Strongylus vulgaris. Twelve samples presented nucleotide sequences for S. vulgaris. In the end, this study revealed the high frequency (96.3%) of S. vulgaris among ponies on farms in Teresópolis, Rio de Janeiro, Brazil.